ANALISIS PRODUKTIVITAS ALAT SLIPFORM PAVER WIRTGEN SP 64 PADA PROYEK JALAN TOL JAKARTA – CIKAMPEK II SELATAN PAKET 2B - Muchamad Al Farizi; Sugiyanto, Martinus Agus (Jurnal Teknik Sipil dan Arsitektur, 2026)
Rigid pavement work on toll road projects requires high equipment productivity so that targets for volume, quality, and execution time can be achieved optimally. One piece of equipment widely used in rigid pavement work is the Wirtgen SP 64 slipform paver because it is capable of carrying out the concrete paving process continuously, precisely, and efficiently. This study aims to analyze the actual productivity and work efficiency of the Wirtgen SP 64 slipform paver on the Jakarta–Cikampek II Selatan Toll Road Project Package 2B, Sukaragam–Bojongmangu Section. The research method used is a quantitative descriptive method with a direct field observation approach. The primary data collected include working time, concrete unloading time, concrete volume, number of dump truck trips, and work duration for each STA segment. The results show that the actual productivity of the equipment ranges from 33.30 m³/hour to 37.24 m³/hour, with an average of 35.60 m³/hour. The highest productivity occurred at STA 29+250–29+550 L2 at 37.24 m³/hour, while the lowest productivity occurred at STA 29+405–29+650 L1 at 33.30 m³/hour. Efficiency based on work volume ranged from 79% to 99%, while efficiency relative to the batching plant capacity of 90 m³/hour ranged from 37% to 41.37%. Overall, the Wirtgen SP 64 slipform paver showed fairly stable, effective, and consistent performance in supporting rigid pavement work. Keyword: Productivity, Slipform Paver Wirtgen SP 64, Rigid Pavement, Efficiency.